The Perception of Cia-Cia Tribe Students in Southeast Sulawesi Toward South Korea: The Case of Education Aid for Cia-Cia Language Preservation - Darynaufal Mulyaman; Asra Virgianita; Darang Sahdana Candra (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2021)
Since the beginning of the